Tahap tekanan akademik dan kerisauan pelajar mempelajari komponen teras Kemahiran Hidup - Mahyuddin, Rahil; Lope Pihie, Zaidatol Akmaliah; Yaacob, Noran Fauziah (Universiti Putra Malaysia Press, 2001)
The purpose of this study was to identify stress and anxiety level of students in learning the core component of the Living Skills (Kemahiran Hidup) subject. Most of the subjects (76.7%) were secondary school students, the others were university student teachers majoring in vocational education. Stress was measured by using items developed by the researchers. Students felt most stressed when they fele guilty because they failed to achieve what was expected of them, and felt uneasy while waiting for the living skills examination results. Several qualitative research findings related to factors contributing LO stress and anxiety were discussed. The researchers had listed several practical recommendations to handle students academic stress in learning the living skills subject. The teaching and learning process for manipulative skills as well as the commerce and entrepreneurship components need to be improved to reduce students' stress.